The Influence of E-Business Adoption and Its Impact on the Business World - Zein, Afrizal (Journal of Social Science and Business Studies, 2025)
The rapid advancement of digital technologies has significantly transformed the business landscape, driving the adoption of e-business practices across industries. This study examines the influence of e-business adoption and its subsequent impact on the business world. By leveraging digital tools and platforms, e-business enables organizations to optimize operations, enhance customer engagement, and access broader markets. The research highlights key factors influencing e-business adoption, including technological readiness, organizational resources, and market dynamics. Furthermore, it evaluates positive outcomes such as increased operational efficiency, improved decision-making through data analytics, and the facilitation of innovative business models. However, cybersecurity risks, digital divide issues, and resistance to change are also discussed. The findings emphasize the strategic importance of e-business as a driver of competitiveness and growth, offering insights for businesses aiming to thrive in the digital economy.